LINKAGES BETWEEN BANK COMPETITION AND FINANCIAL STABILITY: A COMPARATIVE STUDY OF SHARIA VS CONVENTIONAL BANKING IN INDONESIA - Wahyudi, Setyo Tri; Badriyah, Nurul; Nabella, Rihana Sofie; Sari, Kartika; Radeetha, Radeetha (Fakultas Ekonomi dan Bisnis, UNTAN, 2023)
Banking is one of the most important sectors supporting a country